Coagulation Performance of Moringa Oleifera Seeds Stored Under Different Preservation Conditions - Ng, Shu Chin (2006)
The present study was carried out to investigate the effects of storage temperature and packaging methods on the performance of non freeze-dried and freeze-dried Moringa oleifera seeds powders in coagulation of synthetic turbid water (2005 NTU). Non freeze-dried Moringa oleifera was stored in different packaging namely open container, closed container and vacuum packing. Whilst, freeze-dried Moringa oleifera was stored in closed container and vacuum packing. Each of the packaging was kept in room temperature (30°C to 32°C) and refrigerator (4°C). The turbidity, pH and zeta potential of the water samples, the moisture content and physical appearance of Moringa oleifera were examined at monthly interval for 12 months.